Knowledge level of sunflower farmers under public and private extension systems: Knowledge level of sunflower farmers under public and private extension systems - BHUMIREDDY CHANDHANA; G D S KUMAR; R S SENGAR (Journal of Oilseeds Research, 2023)
A test was constructed to measure the farmers’ knowledge level on sunflower cultivation and administrated to 183 and 167 farmers under public and private extension systems, respectively. The farmers were selected from Chikballapur, Kadapa, Nizamabad and Raigarh districts of Karnataka, Andhra Pradesh, Telangana and Chhattisgarh states. The item analysis indicated significant differences in knowledge level of farmers on best season to grow sunflower crop, most suitable period of sowing sunflower crop during Rabi, suitable sunflower hybrids, application of fertilizers and bee keeping increases yield in sunflower under public and private extension systems.